PENGEMBANGAN MEDIA BOOKLET BERBASIS KEARIFAN LOKAL BLITAR PADA PEMBELAJARAN IPS MATERI PENINGGALAN SEJARAH DI SDN NGADIREJO 01 KOTA BLITAR - Muhammad Nurkholis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the limited use of interesting and easy-to-understand digital media that can motivate students to learn. The aim of this research is to produce valid and practical learning media using historical heritage material for class IV elementary school using booklets for social studies learning and to determine the validity and practicality of the media developed. The type of research used is development research (RandD). The Addie development model has 5 development processes, namely: analysis, design, development, implementation and evaluation. The subjects of this research were 3 professionals, namely media experts, 1 teacher, and 21 class IV students at SDN Ngadirejo 01 Blitar City. The results of research conducted through the application of booklets in educational media obtained a validity level of 93.80% in terms of language, 94.10%, and in terms of material, 90.00%. Based on the results of the answers from teachers and students at school, it can be seen that learning using learning media, the teacher response rate at SDN Ngadirejo 01 Blitar City was 88.75%, while the students' answers were 90.00%. Thus, it can be concluded that the learning material using booklets in integrated thematic subjects in class IV elementary school is declared valid and practical to use in the learning process.